1996
DOI: 10.1136/bmj.313.7057.583
|View full text |Cite
|
Sign up to set email alerts
|

Category of exposure to HIV and age in the progression to AIDS: longitudinal study of 1199 people with known dates of seroconversion

Abstract: There was no evidence of differences in rate of development of AIDS by exposure category, while there was a strong tendency for more rapid development in older subjects for all three groups. This supports the view that external cofactors do not play major role in AIDS pathogenesis but that age is of fundamental importance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
43
3
1

Year Published

1997
1997
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(49 citation statements)
references
References 28 publications
2
43
3
1
Order By: Relevance
“…This finding may be explained by the fact that older patients tend to be more adherent and therefore they may experience better virological responses, but also, for a given VL, older patients are less likely to show a recovery in CD4 cell count because of possible reductions in thymic function and the production of naïve T cells [25].…”
Section: Discussionmentioning
confidence: 78%
“…This finding may be explained by the fact that older patients tend to be more adherent and therefore they may experience better virological responses, but also, for a given VL, older patients are less likely to show a recovery in CD4 cell count because of possible reductions in thymic function and the production of naïve T cells [25].…”
Section: Discussionmentioning
confidence: 78%
“…Our results show that the proportion of persons with a short interval is larger in the border region than elsewhere in the United States (CDC, 2008a). Among males, the number with a short interval increased with age, which may be explained by the fact that HIV disease tends to progress more rapidly among older persons (Pezzotti et al, 1996). Another possible explanation is that older persons are assumed not to be at risk and therefore are not the focus of testing programs.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, patients over 50 years old lost the recovered CD4 cells in a median of 7.9 months, while patients under 35 years old returned to their nadir count in double the time (Table 3). Age at infection was one of the most widely recognized risk factors for progression to AIDS in the pre-ART era [22][23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, patients over 50 years old lost the recovered CD4 cells in a median of 7.9 months, while patients under 35 years old returned to their nadir count in double the time (Table 3). Age at infection was one of the most widely recognized risk factors for progression to AIDS in the pre-ART era [22][23][24][25].Pre-ART HIV RNA levels were not available for almost a third of the patients in the study cohort. Using estimates of the missing data, as described in the statistical analysis section, we found that patients with higher HIV RNA levels lost the CD4 cells recovered during therapy more quickly.…”
mentioning
confidence: 99%